Considerations on what constitutes a ‘qualified statistician’ in regulatory guidelines - Gerlinger, Christoph; Edler, Lutz; Kieser, Meinhard; Victor, Norbert (Statistics in medicine, 2012)
International regulatory guidelines require that a ‘qualified statistician’ takes responsibility for the statistical aspects of a clinical trial used for drug licensing. No consensus on what constitutes a ‘qualified statistician’ appears to have been developed so far. The International Society for Clinical Biostatistics is issuing this reflection paper in order to stimulate a discussion on the concept. Copyright © 2011 John Wiley & Sons, Ltd.